Experimental evaluation of RAFT-based Poly(N-isopropylacrylamide) (PNIPAM) kinetic hydrate inhibitors. (1st January 2019) - Park, Juwoon; Kim, Hyunho; da Silveira, Kelly Cristine; Sheng, Qi; Postma, Almar; Wood, Colin D.; Seo, Yutaek
Highlights: RAFT polymerization was applied to generate architecturally defined KHIs. Linear and branched PNIPAM were fully evaluated while varying the cooling rate. Our results suggest a possible new mechanism for managing hydrate formation with a branched PNIPAM. This study provided a better understanding of the architecture-property effect on hydrate prevention. Abstract: As the oil and gas industry produces hydrocarbons from deeper waters and colder regions the issue of hydrate formation becomes more serious. As a result, hydrate inhibition has focused on kinetic hydrate inhibitors (KHI) and anti-agglomerants (AA) as an alternative to the existing approaches which involves injecting vast quantities of thermodynamic inhibitors. In this research, we evaluated the effect of different architectures (linear and branched) of poly( N -isopropylacrylamide) (PNIPAM) polymers synthesized using reversible addition−fragmentation chain-transfer (RAFT) polymerization. Unlike non-reversible deactivation radical polymerisation (RDRP) synthetic routes this generates accurately controlled KHI candidates with target molecular weight, narrow molecular weight distributions and controlled architecture, so that the effect on hydrate inhibition can be more accurately assessed. The RAFT-based polymers (linear and branched) were compared to a commercially available linear PNIPAM synthesized via non-RDRP radical polymerization and control groups (pure water, PVP, and Luvicap). The hydrate experiments were performed in a high pressure autoclave with continuous cooling under different cooling rates (0.25 K/min, 0.033 K/min, and 0.017 K/min). In addition, a cold restart was simulated using constant subcooling. The results regarding subcooling temperature, onset time, and hydrate fraction with resistance-to-flow were compared to known KHIs. These revealed that a linear PNIPAM-MacroRAFT polymer delayed the hydrate nucleation with similar performance to known KHIs (eg., PVP and Luvicap). However, a branched polymer showed the best performance in terms of hydrate fraction and resistance-to-flow among all of the systems tested in this study. These data provide valuable information regarding linear and branched PNIPAM-MacroRAFT polymers by demonstrating their ability to delay hydrate formation but also in preventing hydrate agglomeration. These findings confirm that polymer architecture can effect hydrate inhibition.